2009
DOI: 10.5424/sjar/2009074-1094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum antibodies to bovine herpesvirus-1 in cattle in Galicia (NW Spain)

Abstract: Infectious bovine rhinotracheitis (IBR) is a highly infectious disease of cattle caused by bovine herpesvirus 1 (BHV-1) that causes considerable economic losses to the dairy and beef industry. This report describes the results of two surveys in which prevalence of serum antibodies against BHV-1 in Galicia (NW Spain) was determined. The first was performed on the entire cattle population of the region (year 2000) and the second on the herds included in a voluntary livestock health programme, which comprises IBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…However, the prevalences in this study are lower than those reported by Córdova-Izquierdo et al (2007) in humid tropics of Mexico (90%). Seroprevalences of BoHV-1 in the literature range from 7.5 up to 70.89 % (Solis-Calderon et al, 2003;Eiras et al, 2009;Gupta et al, 2010;Cedeño et al, 2011;Raizman et al, 2011;Yousef et al, 2013;Saravanajayam et al, 2015). The seroprevalence found in this study for BoHV-1, indicates that it is a widely distributed infection in the region.…”
Section: Discussionsupporting
confidence: 52%
“…However, the prevalences in this study are lower than those reported by Córdova-Izquierdo et al (2007) in humid tropics of Mexico (90%). Seroprevalences of BoHV-1 in the literature range from 7.5 up to 70.89 % (Solis-Calderon et al, 2003;Eiras et al, 2009;Gupta et al, 2010;Cedeño et al, 2011;Raizman et al, 2011;Yousef et al, 2013;Saravanajayam et al, 2015). The seroprevalence found in this study for BoHV-1, indicates that it is a widely distributed infection in the region.…”
Section: Discussionsupporting
confidence: 52%
“…In Portugal, the prevalence is 47.2%, in dairy herds in Italy from 61 to 84%, for beef herds 59% and for mixed herds 89%. In Spain, the prevalence is between 38.4% and 50.4% Eiras et al (2009). In Belgium, the positivity rate for dairy herds is 35%, for beef cows 31% and for mixed herds 43% (Boelaert et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in Spain, BVDV and BoHV-1 control programs are voluntary, and only implemented in some regions. In fact, in Galicia (northwestern Spain), the program for both diseases is voluntary (Lindberg et al, 2006;Eiras et al, 2009). However, since September 2019, a volun- tary control program for BoHV-1 has been created in Spain (Royal Decree 554/2019; BOE, 2019).…”
Section: Discussionmentioning
confidence: 99%